2017
DOI: 10.1186/s40648-017-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Wearable finger pad deformation sensor for tactile textures in frequency domain by using accelerometer on finger side

Abstract: In this study, we set out to develop a method for estimating the fine and fast shear deformation of a finger pad, that is, the palm side of a fingertip, as it scans the surface of a material. Using a miniature accelerometer, we measured the acceleration at the radial skin, the deformation of which is accompanied by the shear deformation of the finger pad. Using a transfer function, as specified in a separate experiment, between the pad and side of a finger, we estimated the shear deformation of the finger pad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Similar to our prototype, other earlier studies have successfully expressed the deformation of the fingertip's skin as caused by the tangential force on the fingertip by using a spring-mass-damper model [44][45][46], thereby indicating a linear relationship between the deformation and force. This assumption holds provided that the skin deformation is insignificant and the normal load on the finger is constant, which has typically been observed and recorded during exploratory procedures (EPs) [23].…”
Section: Background and Related Workmentioning
confidence: 69%
“…Similar to our prototype, other earlier studies have successfully expressed the deformation of the fingertip's skin as caused by the tangential force on the fingertip by using a spring-mass-damper model [44][45][46], thereby indicating a linear relationship between the deformation and force. This assumption holds provided that the skin deformation is insignificant and the normal load on the finger is constant, which has typically been observed and recorded during exploratory procedures (EPs) [23].…”
Section: Background and Related Workmentioning
confidence: 69%
“…However, the simulated sensation was not perceived as realistic when the button was pressed too fast. Additional research demonstrated that the deformation of the skin caused by the tangential force on the fingertip can be expressed by using a spring-mass-damper model, indicating a linear relationship between deformation and force [39]. Research by Kaaresoja at Nokia focused on the implementation of vibrotactile feedback accompanied by visual and audio feedback to find latency thresholds required to make virtual button presses feel natural [40].…”
Section: Research On Force Feedback Applications At Jnd Levelmentioning
confidence: 99%
“…This result implies that the deformation of the finger pad's skin along the normal direction mainly determined by surface asperities and the tangential deformation caused by friction may play different roles in texture perception [18,40]. One-dimensional quantities pertaining to skin deformation were measured in many studies related to the normal deformation [6,56], tangential deformation [13,45,48,57], or whole finger vibration [51], where skin deformation and texture perception were discussed. The information related to deformation or vibration in different dimensions is closely coupled, because they propagate in the fingertip.…”
Section: Effectiveness Of Combined Vibrotactile and Electrostatic Stimentioning
confidence: 99%